Global research trends in inflammaging from 2005 to 2024: a bibliometric analysis - Jiang, Beier; Dong, Yi-ni; Xiong, Yu; Jiang, Chun-xia; Ping, Jun; Wu, Qi; Xu, Liu-jun; Shu, Run-zhe; Gao, Dan-dan; Zhu, Sheng-mei; Ye, Wei-dong; Zhang, Feng (Frontiers in Aging, 2025)
BackgroundInflammaging, defined as chronic low-grade inflammation associated with aging, is considered a key factor in many age-related diseases. Despite growing research, comprehensive assessments of trends and focuses on this field over the past 2 decades remain lacking.ObjectiveTo comprehensively analyze literature development trends, scientific priorities, and their evolution in the field of inflammaging from 2005 to 2024 using bibliometric analysis.MethodsAcademic literature on inflammaging was retrieved from the Web of Science Core Collection. CiteSpace software was used as the bibliometric tool to analyze annual publication trends, contributing countries/regions, leading research institutions, primary journals, and keyword co-occurrence, including clustering and burst analysis in this field.ResultsThe study included 1,800 eligible articles, demonstrating a consistent growth in research publications over the past 20 years. The United States and Italy were the principal contributors. The University of Bologna had the highest publication. Professor Claudio Franceschi has been a leading figure in this field. Journal analysis shows that research themes predominantly focus on molecular biology/immunology and medicine/clinical fields. Keyword analysis identifies major research hotspots as “inflammaging,” “Crohn’s disease,” “periodontitis,” “immunosenescence,” “skeletal muscle,” “gut microbiota,” and “Parkinson’s disease.” Emerging term analysis indicates a shift from specific inflammatory diseases to broader aging and immune modulation studies.ConclusionThis first systematic assessment of literature trends in the field of inflammaging from 2005 to 2024 reveals sustained academic growth and an increasingly deep research focus.